The Battery and the Boiler: Adventures in Laying of Submarine Electric Cables - Ballantyne, R. M. (Robert Michael), 1825-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Battery and the Boiler: Adventures in Laying of Submarine Electric Cables" by R.M. Ballantyne is a historical narrative written in the mid-19th century. The book follows the adventures of a boy named Robin Wright, who is born in tumultuous conditions at sea and grows up curious about the science of electricity and telegraphy. As he matures, he becomes embroiled in the fascinating world of submarine cables, aspiring to contribute to the revolutionary efforts of connecting distant lands through this new technology. The opening of the book introduces Robin's dramatic birth during a storm on an emigrant ship and paints a vivid picture of his early life, filled with curiosity and inquisitiveness. As a child, he displays a natural affinity for science, particularly electricity, which is nurtured by his family and his older cousin, Sam. Through entertaining exchanges and adventures, Robin's character is developed as someone who is determined to explore and understand the natural world. The stage is set for his future endeavors, as he prepares to join the electrically charged atmosphere of submarine cable laying$1 (Ba theme that promises both excitement and discovery throughout the narrative. (This is an automatically generated summary.)s
Release date is 2007-06-07
Produced by Nick Hodson of London, England
Keywords: Conduct of life -- Juvenile fiction; Pirates -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Seafaring life -- Juvenile fiction; Uncles -- Juvenile fiction; Cables, Submarine -- Juvenile fiction; Electricity -- Juvenile fiction